Measuring vulnerability index for managing COVID-19 behaviour in Ghana - Mohammed Amidu; Agnes Akpene Akakpo; Teddy Ossei Kwakye (Cogent Business & Management, 2024)
This paper investigates the implications of human behaviour and government support for the quality of life of vulnerable populations during the Covid-19 pandemic. We sample 2,697 households and employ the COM-B model, theory of economic contagion, and information asymmetry to empirically respond to the following research questions: What is the level of vulnerability among informal settlements in Ghana? Did the support vulnerable populations receive during the peak of the Covid-19 outbreak in Ghana improve their state of being? What were the lifestyle changes during the pandemic? Our core finding is that the plight of the vulnerable population is ameliorated when government support brings about positive change in Covid-19 behaviour. Our analysis suggests that cash transfers, free utilities and credit schemes reduce income vulnerability. Moreover, government support for small businesses and tax exemption have the potential of reducing employment vulnerability. It is therefore recommended that policymakers should institutionalize emergency cash transfers, subsidize essential utilities, and establish accessible credit schemes to support vulnerable populations after the Covid-19 crisis.
Keywords: 650; COVID-19; ghana; global pandemics; vulnerable population